2022
DOI: 10.1186/s12872-022-02892-3
|View full text |Cite
|
Sign up to set email alerts
|

Symptom recognition and treatment-seeking behaviors in women experiencing acute coronary syndrome for the first time: a qualitative study

Abstract: Background Women are more likely to delay medical help-seeking for ACS symptoms. Understanding patients’ experience of the symptoms and their response is essential in improving help-seeking behaviors and timely diagnosis and treatment for ACS. This study aimed to explore women’s experience of ACS, their response to the symptoms, and treatment-seeking decisions. Methods This qualitative descriptive study was conducted in a tertiary referral special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Similarly, tendency to choose self-treatment by using home remedies to solve their symptoms was also found by previous study among women in Middle East country [25]. A previous review found that low intensity symptoms were considered as not serious disease then leading patients to delay for seeking medical helps [26] or just wait and believe that the symptoms will…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, tendency to choose self-treatment by using home remedies to solve their symptoms was also found by previous study among women in Middle East country [25]. A previous review found that low intensity symptoms were considered as not serious disease then leading patients to delay for seeking medical helps [26] or just wait and believe that the symptoms will…”
Section: Discussionmentioning
confidence: 73%
“…This study provided insight into treatment seeking behaviour, barriers and enabling factors for seeking medical treatment, and experiences after entering hospitals, communicating with healthcare staffs, and receiving medical treatment for ACS patients during the COVID-19 pandemic. We found that treatment seeking decision was aligned with the evidences prior to the pandemic in that mild ACS symptoms led to the delay in seeking medical treatment [ 25 28 ]. When symptoms were mild, such as fatigue and tiredness, patients might misinterpret and believed that these symptoms were caused by hard work and could be fully recovered in a few days without specific medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a qualitative study in Iran of 39 women with first-time ACS that found women tended to delay seeking help when their symptoms were mild and developed gradually. Women often underestimated the symptoms and attributed them to noncardiac causes, making them more likely to delay seeking treatment for CHD symptoms [ 32 , 33 ]. Our findings were also in line with a study of Pakistani society, which showed that, because women are overburdened with their family and household responsibilities, many are unaware of or fail to pay attention to symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(*) Semi-structured interview: Interviews will last a maximum of 45 min, and will include open-ended questions regarding (1) the patient's experiences from the onset of symptoms to the decision to seek medical attention; (2) questions about patients' physical and emotional feelings during the experience, decision-making processes (e.g., who they talked to and who they asked for advice), and beliefs about what was happening at the onset of myocardial infarction symptoms. A matrix of structured interview questions was developed specifically for this study based on a literature review that examined the concepts and factors associated with women's delay in seeking medical care [24,47,48]. The interviews will be conducted during the patient's hospitalization or 2-3 months after discharge, as in the study by Blakeman et al [49].…”
Section: Study Measurement Toolsmentioning
confidence: 99%